Prospective Multicentre Cohort Study of Fenestrated and Branched Endografts After Failed Endovascular Infrarenal Aortic Aneurysm Repair with Type Ia Endoleak. (October 2021) - Hostalrich, Aurélien; Mesnard, Thomas; Soler, Raphael; Girardet, Paul; Kaladji, Adrien; Jean Baptiste, Elixéne; Malikov, Serguei; Reix, Thierry; Ricco, Jean-Baptiste; Chaufour, Xavier
Abstract : Objective: Failed endovascular infrarenal aortic aneurysm repair (EVAR) due to development of late type Ia endoleak exposes patients to the risk of rupture and should be treated. The purpose of this study was to evaluate the results of fenestrated/branched EVAR (F/BEVAR) for treatment of failed EVAR with type Ia endoleak. Methods: From January 2010 to December 2019, a prospective multicentre study was conducted (ClinicalTrials.gov identifier: NCT04532450) that included 85 consecutive patients who had undergone F/BEVAR to treat a type Ia endoleak following EVAR. The primary outcome was overall freedom from any re-intervention or death related to the F/BEVAR procedure. Results: In 30 cases (35%) EVAR was associated with a short < 10 mm or angulated (> 60°) infrarenal aortic neck, poor placement of the initial stent graft ( n = 3, 4%), sizing error ( n = 2, 2%), and/or stent graft migration ( n = 7, 8%). Type Ia endoleak was observed after a period of 59 ± 25 months following EVAR. The authors performed 82 FEVAR (96%) and three BEVAR (4%) procedures with revascularisation of 305 target arteries. Overall technical success was 94%, with three failures including one persistent Type Ia endoleak and two unsuccessful stent graft implantations. Intra-operative target artery revascularisation was successful in 303 of 305 attempts. The in hospital mortality rate was 5%. Cardiac, renal and pulmonary complications occurred in 6%, 14%, and 7% of patients, respectively. Post-operative spinal cord ischaemia occurred in four patients (4.7%). At three years, the survival rate was 64% with overall freedom from any re-intervention or aneurysm related death of 40%, and freedom from specific F/BEVAR re-intervention of 73%. At three years, the secondary patency rate of the target visceral arteries was 96%. During follow up, 27 patients (33%) required a revision procedure of the fenestrated ( n = 11) or index EVAR stent graft ( n = 16), including six open conversions. Conclusion: While manufactured F/BEVAR was effective in treating type Ia endoleak in patients with failed EVAR, it was at the cost of a number of secondary endovascular and open surgical procedures.